Poisoning of sheep by Vernonia plantaginoides (Less.) Hieron in Uruguay. (July 2016) - Dutra, Fernando; Romero, Agustin; Quinteros, Carina; Araújo, Ruben; García y Santos, Carmen
Vernonia plantaginoides (Less.) Hieron, previously known as Vernonia squarrosa, is a rhizomatous subshrub with purple flowers that is prevalent in the natural grassland of Uruguay, Argentina, and southern Brazil. We report an outbreak of V. plantaginoides ( yuyo moro ) intoxication in sheep in Treinta y Tres Department, northeastern Uruguay. A total of 54 of 463 (12%) recently weaned lambs died 2–7 days after entering a natural pasture that had been invaded by sprouting V. plantaginoides . The first cases were found dead. Affected lambs showed marked jaundice, edema of the face, ears, and eyelids, and severe photodermatitis. At the autopsies of 3 lambs, the carcass was yellow, the liver was enlarged with a marked acinar pattern ("nutmeg liver"), and hemorrhages were observed on serous membranes. Microscopic lesions were characterized by diffuse periacinar hepatocellular necrosis and cholemic nephrosis. Three female lambs were experimentally dosed with the aerial parts of V. plantaginoides collected immediately after the outbreak. The lamb that was dosed once with 40 g/kg body weight died after 36 h with severe hepatic necrosis. The lamb dosed with 20 g/kg daily for 4 days showed clinical signs and microscopic lesions in the liver with multiple apoptotic hepatocytes in the periacinar zone. The third lamb, dosed with 30, 17, and 15 g/kg daily over 3 days, respectively, showed transient clinical signs and a rise in liver enzymes, but recovered, and no lesions were found postmortem. These results demonstrate that V. plantaginoides was responsible for severe field outbreaks of poisoning in sheep in Uruguay.